Differential Methylation of Genes in the Medial Prefrontal Cortex of Developing and Adult Rats Following Exposure to Maltreatment or Nurturing Care During Infancy - Blaze, Jennifer; Scheuing, Lisa; Roth, Tania L. (Developmental neuroscience, 2013)
Quality of maternal care in infancy is an important contributing factor in the development of behavior and psychopathology. One way maternal care could affect behavioral trajectories is through environmentally induced epigenetic alterations within brain regions known to play prominent roles in cognition, emotion regulation, and stress responsivity. Whereas such research has largely focused on the hippocampus or hypothalamus, the prefrontal cortex (PFC) has only just begun to receive attention. The current study was designed to determine whether exposure to maltreatment or nurturing care is associated with differential methylation of candidate gene loci (bdnf and reelin) within the medial PFC (mPFC) of developing and adult rats. Using a within-litter design, infant male and female rats were exposed to an adverse or nurturing caregiving environment outside their home cage for 30 min per day during the first postnatal week. Additional littermates remained with their biological caregiver within the home cage during the manipulations. We observed that infant rats subjected to caregiver maltreatment emitted more audible and ultrasonic vocalizations than littermates subjected to nurturing care either within or outside of the home cage. While we found no maltreatment-induced changes in bdnf DNA methylation present in infancy, sex-specific alterations were present in the mPFC of adolescents and adults that had been exposed to maltreatment. Furthermore, while maltreated females showed differences in reelin DNA methylation that were transient, males exposed to maltreatment and both males and females exposed to nurturing care outside the home cage showed differences in reelin methylation that emerged by adulthood. Our results demonstrate the ability of infant-caregiver interactions to epigenetically mark genes known to play a prominent role in cognition and psychiatric disorders within the mPFC. Furthermore, our data indicate the remarkable complexity of alterations that can occur, with both transient and later emerging DNA methylation differences that could shape developmental trajectories and underlie gender differences in outcomes.